2009
DOI: 10.1016/j.bmcl.2009.08.095
|View full text |Cite
|
Sign up to set email alerts
|

A naturally occurring brominated furanone covalently modifies and inactivates LuxS

Abstract: Halogenated furanones, a group of natural products initially isolated from marine red algae, are known to inhibit bacterial biofilm formation, swarming, and quorum sensing. However, their molecular targets and the precise mode of action remain elusive. Herein, we show that a naturally occurring brominated furanone covalently modifies and inactivates LuxS (S-ribosylhomocysteine lyase, EC 4.4.1.21), the enzyme which produces autoinducer-2 (AI-2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 34 publications
1
57
0
3
Order By: Relevance
“…One such furanone, designated C-2 (Table 3), was further characterized mechanistically and was found to covalently modify LuxS, resulting in a single LuxS adduct detectable by mass spectrometry. Matrix-assisted laser desorption ionization (MALDI)-MS results were consistent with the loss of one bromide atom from C-2 following modification of LuxS (147). The mechanisms of the remaining furanone inhibitors were not elucidated.…”
Section: Inhibition Of Ai-2 Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…One such furanone, designated C-2 (Table 3), was further characterized mechanistically and was found to covalently modify LuxS, resulting in a single LuxS adduct detectable by mass spectrometry. Matrix-assisted laser desorption ionization (MALDI)-MS results were consistent with the loss of one bromide atom from C-2 following modification of LuxS (147). The mechanisms of the remaining furanone inhibitors were not elucidated.…”
Section: Inhibition Of Ai-2 Productionmentioning
confidence: 95%
“…There has also been a single report of inhibition by covalent modification of LuxS. Bromonated furanones have long been recognized as inhibitors of AHL-mediated quorum sensing in Gram-negative bacteria (see "Furanones" below), and Zang et al identified multiple brominated furanones that inhibited LuxS to various degrees (147). One such furanone, designated C-2 (Table 3), was further characterized mechanistically and was found to covalently modify LuxS, resulting in a single LuxS adduct detectable by mass spectrometry.…”
Section: Inhibition Of Ai-2 Productionmentioning
confidence: 99%
“…However, LuxS is also a central metabolic enzyme which plays a crucial role in methionine metabolism [20] and participates in protein, RNA, and DNA synthesis [17], and therefore, the effects observed when its gene is mutated have to be interpreted carefully. Furanones, which are known to inhibit communication based on acyl homoserine lactone (AHL) and AI-2 signals [21], have been reported to affect biofilm formation in S. mutans . A previous study indicated that the biofilm inhibition observed in S. mutans supplemented with the furanone C52 is linked with the interference with AI-2-controlled processes [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several naturally occurring brominated furanones were demonstrated to be able to covalently modify and inhibit the LuxS enzyme in a concentration-dependent manner (Zang et al 2009). Lately, several brominated furanone derivatives were synthesised by Benneche and co-workers and investigated for their ability to interfere with QS process using the reporter bacterial strain V. harveyi.…”
Section: Targeting the Ai-2 Synthasesmentioning
confidence: 98%